Assessment Of Aboveground Biomass And Temperature In The Tropical Rainforest Of Malaysia - Azmi, Ezzatul Farhain; Hussin, Nor Hafizah; Syed Ahmad, Sharifah Sakinah; Mohd Said, Rahaini; Samsudin, Adam (Blue Eyes Intelligence Engineering and Sciences Publication, 2019)
The relation between tropical rainforest to the climate variability is very important. This research aims to determine the relationship between aboveground biomass which prefer tree in the tropical rainforest and surrounding temperature. Diameter at breast height (DBH) of ten tree species and surrounding temperature collected data were taken to measure the correlation between the two variables by using statistical test. Furthermore, forest biomass estimation is also important towards the assessment of the productivity, structure and forest condition. The analysis in this research shows that simple linear regression model can be used to predict the future value of DBH for each species. The findings may help the reduction of greenhouse gas emissions with proper conservation and sustainable management.